Red Blood Cell Transfusion and its Relationship with Pedicle Thrombosis in Microvascular Free Flaps - Torres Fuentes, Carlos Eduardo; Rodríguez Mantilla, Iván Enrique; Cáceres, Diego Nicolás Guerrero; Camargo Gonzalez, Diego Felipe (Journal of Reconstructive Microsurgery, 2021)
Background Free flaps have become a highly valuable tool for complex reconstructive surgeries. The requirement of red blood cell transfusion (RBCT) during the perioperative period is common and its effect on the free flap survival is debatable. The aim of this study was to determine the relationship between perioperative RBCT and vascular pedicle thrombosis (VPT).Methods For this study 302 free flaps performed between January 2006 and December 2019 were retrospectively analyzed. It included their characteristics from before, during, and after the surgical procedure. The incidence of VPT and flap survival were calculated based on Kaplan Meier's method and the relationship between VPT and perioperative variables were analyzed by Cox regression models.Results The transfusion group was represented by 62 flaps (20.5%) and no transfusion by 240 flaps. The overall transfusion requirement was 20.5% and the cumulative incidence of VPT was 9.11%. A statistically significant relationship was not demonstrated between flap survival and transfusion status (HR = 1.73 IC 95%: 0.5 to 3.96; p = 0.192) (p = 0.192) independently from the number of units transfused, the preoperative diagnosis of anemia, and the type of flap used and did not establish an increased risk of VPT.Conclusion This study did not demonstrate an association between RBCT during preoperative period and the risk for VPT or microvascular free flap survival rate on postoperative follow up.
Keywords: free flap; thrombosis; blood transfusion